1990
DOI: 10.3382/ps.0692008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Vitamin D3, 1α-Hydroxyvitamin D3, and 1,25-Dihydroxyvitamin D3 on Eggshell Quality, Tibia Strength, and Various Production Parameters in Commercial Laying Hens

Abstract: Four hundred 53-wk-old Hyline W36 laying hens were randomly allocated to 10 treatments. The effects of feeding two vitamin D3 metabolites, 1 alpha-hydroxyvitamin D3 [1 alpha-(OH) D3] and 1,25-dihydroxyvitamin D3 [1,25-(OH)2 D3], each at five dietary levels (0, .75, 1.50, 3.00, and 4.50 micrograms/kg of feed) were determined on eggshell quality and tibia strength in commercial laying hens (Experiment 1). In Experiment 2, 1,440 Hyline W36 65-wk-old laying hens were used to determine the effects of four levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 18 publications
2
17
0
4
Order By: Relevance
“…Similar results were reported by Frost & Roland (1990) using increasing levels of vitamin D 3 (0; 500; 1,000 and 1,500 UCI/kg). Those authors verified increase in eggs production and feed intake when the level of vitamin D 3 increased in the feed.…”
Section: Resultssupporting
confidence: 88%
“…Similar results were reported by Frost & Roland (1990) using increasing levels of vitamin D 3 (0; 500; 1,000 and 1,500 UCI/kg). Those authors verified increase in eggs production and feed intake when the level of vitamin D 3 increased in the feed.…”
Section: Resultssupporting
confidence: 88%
“…In contrast, Frost et al (1990) reported that l,25(OH) 2 D 3 may have an effect on increasing bone mass in laying hens. Values of physical parameters of bones in chickens fed on the diet with the addition of phytase were higher than in the control, which is in agreement with reports of other authors (Perney et al, 1993;Qian et al, 1996;Puzio et al, 2000).…”
Section: Resultsmentioning
confidence: 83%
“…Improvement of dietary calcium and phosphorus utilisation by 1,25(OH) 2 D 3 in the form of dietary SG has been already demonstrated in laying hens (Frost and Roland, 1990).…”
Section: Laying Hensmentioning
confidence: 93%